2016
DOI: 10.1002/he.20211
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Parenthood During Graduate School on PhD Recipients’ Paths to the Professoriate: A Focus on Motherhood

Abstract: This chapter focuses on graduate students who are parents, the career‐related resources they gather during graduate school, and the influence of those resources on PhD‐earning mothers’ attainment of tenure‐track faculty jobs at U.S. higher‐education institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 40 publications
(67 reference statements)
1
34
1
Order By: Relevance
“…Those who are underrepresented due to race/ethnicity, gender, or citizenship are at higher risk of leaving their programs before graduation (McBain, 2019). Women with children, who comprise approximately 7-8% of doctoral students (Golde & Dore, 2001;Kulp, 2016Kulp, , 2019Mason, Goulden, & Frasch, 2009) are one atrisk group. This is particularly relevant within social work doctoral education, as women comprise 75% of social work doctoral students (CSWE, 2018).…”
mentioning
confidence: 99%
“…Those who are underrepresented due to race/ethnicity, gender, or citizenship are at higher risk of leaving their programs before graduation (McBain, 2019). Women with children, who comprise approximately 7-8% of doctoral students (Golde & Dore, 2001;Kulp, 2016Kulp, , 2019Mason, Goulden, & Frasch, 2009) are one atrisk group. This is particularly relevant within social work doctoral education, as women comprise 75% of social work doctoral students (CSWE, 2018).…”
mentioning
confidence: 99%
“…Mothers in academia are more negatively affected by parenthood and marriage than are married men with children and single women without children (Jacobs & Winslow, 2004a, 2004bLynch, 2008;Miller, 2009;Wolf-Wendel & Ward, 2006). Despite the fact that mothers are just as productive as their non-parent counterparts (Kulp et al, 2016), research shows women are more likely than men to hold adjunct teaching positions and are overrepresented in part-time, non-tenure-track jobs, illustrating a clear discrepancy between genders related to academic work (Armenti, 2004;McMahon & Green, 2008). Doctoral students who are mothers are less likely to become socialized into programs and may be less likely to be asked to coauthor papers with advisors and engage in other status-building activities, putting them at a disadvantage when it comes to obtaining tenure at a postsecondary institution (Kennelly & Spalter Roth, 2006;Kulp, 2016).…”
Section: Mothers In Academiamentioning
confidence: 99%
“…Despite the fact that mothers are just as productive as their non-parent counterparts (Kulp et al, 2016), research shows women are more likely than men to hold adjunct teaching positions and are overrepresented in part-time, non-tenure-track jobs, illustrating a clear discrepancy between genders related to academic work (Armenti, 2004;McMahon & Green, 2008). Doctoral students who are mothers are less likely to become socialized into programs and may be less likely to be asked to coauthor papers with advisors and engage in other status-building activities, putting them at a disadvantage when it comes to obtaining tenure at a postsecondary institution (Kennelly & Spalter Roth, 2006;Kulp, 2016). Additionally, Kulp (2016) found that mothers with doctorates tended to take longer to complete the degree and graduated at an older age than their non-parent counterparts.…”
Section: Mothers In Academiamentioning
confidence: 99%
See 1 more Smart Citation
“…Others argue that only the existence of young children decreases the production of publications (Cole and Zuckerman 1984;Mason, Wolfinger, and Goulden 2013;Lutter and Schröder 2019;Fox 2005;Kyvik and Teigen 1996;Long 1992). Still, others consider that women with young children are less likely to get Tenured positions than their childless peers (Kulp 2016;Mason, Wolfinger, and Goulden 2013;Mason and Goulden 2004;Morrison, Rudd, and Nerad 2011). This leads to motherhood being perceived as a "risk" in advancing and consolidating women's careers in the academic field.…”
Section: When Care Enters the Academic Field: Making The Invisible Visiblementioning
confidence: 99%